Fasting during Ramadan in people with chronic kidney disease: a review of the literature - Ahmad, Shahzaib (Ther Adv Endocrinol Metab, 2019)
Chronic kidney disease (CKD) is common among Muslim patients, and many such patients are keen to fast during the month of Ramadan. Fasting for prolonged periods may be deleterious for patients with CKD, but the changing season of fasting means that the duration of fast is very variable between geographical locations. There is, furthermore, a paucity of evidence to guide patients and clinicians in management of fasting in people with CKD. In this article, we aim to review the available evidence for patients with CKD and fasting, including haemodialysis and renal transplantation. We suggest that all patients with CKD should be deemed high risk or very high risk for fasting. We conclude, however, that patients with stable mild/moderate CKD (stage 1–3) may be able to fast providing they are carefully monitored and counselled. We also suggest that patients with stable renal transplants may also be able to fast, providing they are monitored carefully by their transplant team. Patients on haemodialysis or peritoneal dialysis should not be encouraged to fast, but if they do so, they will need careful weekly monitoring. There is an urgent need for high-quality data for patients with CKD who plan to fast over Ramadan, to enable more guidance to be developed for this vulnerable group of patients.